Population analysis of susceptibility to propolis in reference strains of Staphylococcus aureus and Escherichia coli - Fernandes A., Jr [UNESP]; Lopes, C. A M [UNESP]; Sforcin, J. M. [UNESP]; Funari, S. R C [UNESP] (FapUNIFESP (SciELO), 1997)
Susceptibility to several ethanolic extracts of propolis (EEP) concentrations was tested with the population analysis technique in reference strains of Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 35218). The results of these tests showed that all bacteria were killed by EEP concentrations approximately equal or higher (2.0% v/v - S. aureus; 10.0% v/v - E. coli) than the respective minimal inhibitory concentrations (MIC). Regarding the susceptibility to propolis, there was a homogeneity of data with the respective time kill curves showing a clear bactericidal effect during 6 to 9 h of exposition.
Keywords: Escherichia coli; Population analysis; Propolis; Staphylococcus aureus; Susceptibility; propolis; bactericidal activity; escherichia coli; minimum inhibitory concentration; nonhuman; staphylococcus aureus